Peningkatan Kompetensi Guru Sekolah Inklusi melalui Pendampingan Terstruktur (Perencanaan, Tindakan & Pengamatan, dan Refleksi) - Ediyanto; Asep Sunandar; Wiwik Dwi Hastuti; Putri Kartika Ningsih (Jurnal Soeropati, 2021)
Teachers are an important factor in optimizing inclusive education in certain educational units. In addition to classroom teachers, special teachers are also needed who have broad insight and skills in implementing inclusive learning in the classroom. In addition, parental involvement in children's education is a driving and determining factor in the development of inclusive education. Starting from making decisions regarding school placement, to collaboration between the education unit and parents who have children with special needs. With limited understanding and acceptance of the existence of ABK, teachers need skills in learning for ABK. Educational backgrounds that do not provide provisions for special education cause almost all teachers to face problems in dealing with children with special needs. This Community Service Program is one solution in an effort to provide the skills needed by inclusive school teachers at Ma'arif Prison in the form of handling children with special needs and indirectly as a form of improving the quality of learning in the classroom. The results of the pre-test and post-test showed a significant increase in competence in the aspects of awareness, knowledge, and skills of the trainee teachers. The average pre-test score was 54.67, while the post-test average score was 80.56. These results indicate that there is an increase in the understanding of the Ma'arif LP teachers regarding the service framework for inclusive students or with special needs which consists of early detection, consultation, collaboration and counseling. During the mentoring, the participants gave positive feedback on the activities and hoped that further activities would be applicable in relation to the implementation of inclusive education in educational units.